At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's solve the equation step by step.
The given equation is:
[tex]\[ -8c + 13 = -10c - 9 \][/tex]
### Step 1: Move all terms involving [tex]\(c\)[/tex] to one side of the equation
To do this, let's add [tex]\(10c\)[/tex] to both sides to move all [tex]\(c\)[/tex]-terms to the left side:
[tex]\[ -8c + 10c + 13 = -9 \][/tex]
### Step 2: Simplify the equation
Combine the [tex]\(c\)[/tex]-terms on the left side:
[tex]\[ 2c + 13 = -9 \][/tex]
### Step 3: Move the constant term to the other side of the equation
To isolate the [tex]\(c\)[/tex]-term, subtract 13 from both sides:
[tex]\[ 2c + 13 - 13 = -9 - 13 \][/tex]
[tex]\[ 2c = -22 \][/tex]
### Step 4: Solve for [tex]\(c\)[/tex]
Divide both sides of the equation by 2 to solve for [tex]\(c\)[/tex]:
[tex]\[ c = \frac{-22}{2} \][/tex]
[tex]\[ c = -11 \][/tex]
So, the solution to the equation is:
[tex]\[ c = -11 \][/tex]
Thus, the correct option is [tex]\(c = -11\)[/tex].
The given equation is:
[tex]\[ -8c + 13 = -10c - 9 \][/tex]
### Step 1: Move all terms involving [tex]\(c\)[/tex] to one side of the equation
To do this, let's add [tex]\(10c\)[/tex] to both sides to move all [tex]\(c\)[/tex]-terms to the left side:
[tex]\[ -8c + 10c + 13 = -9 \][/tex]
### Step 2: Simplify the equation
Combine the [tex]\(c\)[/tex]-terms on the left side:
[tex]\[ 2c + 13 = -9 \][/tex]
### Step 3: Move the constant term to the other side of the equation
To isolate the [tex]\(c\)[/tex]-term, subtract 13 from both sides:
[tex]\[ 2c + 13 - 13 = -9 - 13 \][/tex]
[tex]\[ 2c = -22 \][/tex]
### Step 4: Solve for [tex]\(c\)[/tex]
Divide both sides of the equation by 2 to solve for [tex]\(c\)[/tex]:
[tex]\[ c = \frac{-22}{2} \][/tex]
[tex]\[ c = -11 \][/tex]
So, the solution to the equation is:
[tex]\[ c = -11 \][/tex]
Thus, the correct option is [tex]\(c = -11\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.